2007
DOI: 10.1200/jco.2006.10.2509
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized Study of Single Compared With Double Autologous Stem-Cell Transplantation for Multiple Myeloma: Bologna 96 Clinical Study

Abstract: In comparison with a single ASCT as up-front therapy for newly diagnosed MM, double ASCT effected superior CR or nCR rate, RFS, and EFS, but failed to significantly prolong overall survival. Benefits offered by double ASCT were particularly evident among patients who failed at least nCR after one autotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
228
5
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(261 citation statements)
references
References 37 publications
15
228
5
13
Order By: Relevance
“…Such high CR and !VGPR rates are important, because it has been demonstrated that CR rates and a !VGPR rates, both postinduction and post-ASCT, are prognostic for improved outcomes. 8,[22][23][24][25][26][27] To date, this is the largest study, with the longest follow-up, to assess BTD induction therapy. The 25-month follow-up allowed an analysis of post-ASCT outcomes to assess the impact of the response and CR rates achieved; and, to our knowledge, this is the first study to report time-to-events data after BTD induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high CR and !VGPR rates are important, because it has been demonstrated that CR rates and a !VGPR rates, both postinduction and post-ASCT, are prognostic for improved outcomes. 8,[22][23][24][25][26][27] To date, this is the largest study, with the longest follow-up, to assess BTD induction therapy. The 25-month follow-up allowed an analysis of post-ASCT outcomes to assess the impact of the response and CR rates achieved; and, to our knowledge, this is the first study to report time-to-events data after BTD induction.…”
Section: Discussionmentioning
confidence: 99%
“…The 25-month follow-up allowed an analysis of post-ASCT outcomes to assess the impact of the response and CR rates achieved; and, to our knowledge, this is the first study to report time-to-events data after BTD induction. Reflecting the association between CR and !VGPR rates and improved outcomes, 8,[22][23][24][25][26][27] the time-to-events data were promising. In addition, analysis of OS post-transplantation according to response to BTD induction therapy suggested a trend toward improved survival in patients who achieved a !VGPR compared with those who did not, although the small number of patients who did not proceed to HDT-ASCT limits interpretation of this result.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a Spanish randomized trial, patients responding to induction therapy failed to benefit from ASCT trial, suggesting that the greatest benefit from early ASCT may be mainly among the small proportion of patients with disease refractory to induction therapy [92]. Two randomized trials have found benefit with tandem (double) versus single ASCT, with the benefit primarily seen in patients failing to achive CR or VGPR with the first ASCT [93,94]. Two other randomized trials, however, have yet to show significant improvement in OS with double ASCT [95,96].…”
Section: Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Most randomised trials comparing single with tandem ASCT have shown no benefit in overall survival from tandem stem cell transplantation (Attal et al, 2003;Fermand et al, 2005b;Cavo et al, 2007;Mai et al, 2016;Sonneveld et al, 2007; reviewed by Kumar et al, 2009). Many of these trials utilised non-standard conditioning regimens (e.g.…”
Section: Tandem Transplantsmentioning
confidence: 99%
“…Many of these trials utilised non-standard conditioning regimens (e.g. oral busulfan or TBI) which have since been shown to be inferior to standard mel200 (Attal et al, 2003;Fermand et al, 2005b;Cavo et al, 2007;Sonneveld et al, 2007). However the GMMG-HD2 trial, which used tandem standard mel200 ASCT, showed no difference in survival (Mai et al, 2016).…”
Section: Tandem Transplantsmentioning
confidence: 99%